Infertility in Women with Polycystic Ovary Syndrome Pathogenesis and Management (Springer International Publishing, 2018)
This book presents up-to-date knowledge on infertility in the context of polycystic ovary syndrome (PCOS) and provides clear evidence-based guidance on its treatment. The book opens by discussing anovulation, oocyte quality, and the endometrium in women with PCOS, infertility and subfertility cofactors, and the impact of PCOS phenotypes on fertility. All aspects of management are then thoroughly addressed. The available medical treatments for PCOS-related infertility - including antiestrogens, aromatase inhibitors, insulin-sensitizing drugs, and gonadotropins - are reviewed, and other potential therapeutic approaches, such as acupuncture and laparoscopic ovarian drilling, are assessed. Careful attention is also devoted to the role of lifestyle interventions. The use of controlled ovarian stimulation in infertile PCOS patients undergoing intrauterine insemination or in vitro fertilization is examined in detail, as are the benefits of in vitro maturation of oocytes. This book will be of value to all who are involved in the care of women with PCOS and related infertility issues. .